Pathological Abnormalities Due to Impaction of Third Molar Mandibular Horizontal and Mesioangular Angulation with Observation of Panoramic Radiography - Savitri, Yunita; Saputra, Deny; Damayanti, Meidy (International Journal of Psychosocial Rehabilitation, 2020)
The lower third molar teeth are the most commonly impacted teeth due to a lack of place for an eruption. Impacted teeth affect the surrounding tissue and can lead to pathological abnormalities. The effect of impacted teeth results in various complaints such as pain, caries, pericoronitis, adjacent tooth root resorption, dentigerous cysts, and odontogenic tumors. The impacted mandibular third molars and associated pathological abnormalities were observed with panoramic radiography. Purpose: To determine the pathological abnormalities that accompany the molar impaction of horizontal and mesioangular angular mandibula with panoramic radiographic observation. Material&Methods: In this study, using the panoramic radiograph, consisting of 53 samples of radiographs were evaluated based on the mesioangular and horizontal angulation of mandibular impacted third molars and pathology abnormalities caused. The data were processed and analyzed by using the Friedman test and Chi-square test. Result: In impaction with mesioangular angulation, bone loss at the interalveolar between third molar and mandibular second molars by 33.3%, caries on the mandibular second molars and mandibular second molar’s root resorption had a similar percentage by 26.7% and caries in mandibular third molar impaction amounted to 13.3%. In impaction with horizontal angulation bone loss at interalveolar third molar and mandibular second molar by 59.1%, mandibular second molars of caries were 22.7%, caries in mandibular third molar impaction and mandibular second molar root resorption by 9.1%. Conclusions: The most common pathological abnormalities in mandibular third molar impaction of mesioangular and horizontal angulation are bone loss in the interalveolar third molar and the mandibular second molar.